Bancos e concentração de crédito no Brasil: 1995-2004 - Daniel Bruno de Castro Almeida (2007)
After stabilization, Brazilian bank system came into a process of concentration. This process follows world trend of bank concentration related with liberalization and deregulation of the sector. This work aims at analyzing the effects of banking concentration on credit concession in Brazil, during the period of 1995 to 2004. In order to accomplish this objective, the thesis estimates a panel based on data from the twenty seven federation units of Brazil, regarding the period. The results reinforce the idea that the consolidation of Brazilian banking system presents a negative effect on credit availability, especially in less developed regions of the country, damaging their economic performance.